Nanotechnology in Livestock Production: A Review (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Nanotechnology , a technology that involves reduction of materials and structures into miniature/minute sizes that perform their functions accurately and better than the bulk size, has its usage in every aspect of life but the use in agriculture remain unharnessed especially in Africa and other developing countries. The areas of use of nanotechnology in the field of livestock production is reviewed in this paper alongside with the challenges and prospects with a view of motivating animal scientists , livestock farmers and other practitioners to adopt the technology in improving livestock productivity, animal health care management and husbandry practices that improve yield and efficiency.
Keywords: Animal health care; Efficiency; Livestock farmers; Nanotechnology; Reduction of materials